The orchid-bee fauna (Hymenoptera: Apidae) of ‘RPPN Feliciano Miguel Abdala’ revisited: relevant changes in community composition - Nemésio,A. (2013)
The orchid-bee fauna of ‘Reserva Particular do Patrimônio Natural Feliciano Miguel Abdala’, a 957-ha preserve of Atlantic Forest in eastern Minas Gerais, southeastern Brazil, was surveyed 12 years after the first inventory in the area. Orchid-bee males were actively collected with insect nets when attracted to seventeen chemical compounds used as scent baits. Three hundred and nineteen males belonging to nine species were collected during 40 hours in late December, 2011, when orchid bees are supposedly more active. Euglossa despecta Moure, 1968, one of the dominant species in the area 12 years ago, was not recorded in the present study. Eulaema nigrita Lepeletier, 1841, on the other hand, represented only 16% of the collected bees in 1999 and 61% in the present study. Possible causes and consequences of these changes are discussed.